Patient and care partner burden in cutaneous T-cell lymphoma using disease-specific measures of symptoms and health-related quality of life - Julia J Scarisbrick; Larisa Geskin; Sima Rozati; Erika Morsia; Koen D Quint; Amy Musiek; Arvind Arumainathan; Jennifer DeSimone; Richard Cowan; Antonio Giordano; Michi M Shinohara; Cristina Muniesa; et al. (British Journal of Dermatology, 2026)
Patients with mycosis fungoides (MF) or Sézary syndrome (SS) may experience visible lesions, severe itch, sleep disturbance, body temperature dysregulation and depression. In this international study, 73 patients completed a symptom diary and questionnaires relating to fatigue and health-related quality of life [HRQoL: the MF/SS-cutaneous T-cell lymphoma QoL measure (MF/SS-CTCL QoL)]; 24 care partners also completed an HRQoL questionnaire. Patients reported a high symptom burden that differed between MF and SS, with a moderate impact on HRQoL. This is the first study to identify which symptoms of MF/SS compromise different aspects of both patients’ and care partners’ HRQoL. Addressing specific skin symptoms may improve patients’ fatigue, sleep and overall HRQoL and care partners’ HRQoL.